A Survey Study On Eco-Friendly Gokulnagar Village of Savar, Dhaka (Journal of Environmental Science and Natural Resources, 2015)
The study carried out in Eco-friendly Gokulnagar village of Saver, Dhaka during March to December 2013. For the specific purpose of study, respective data were collected from primary source as well as secondary source. In primary data collection structured Questionnaire, FGD, PRA techniques as well as sample random sampling techniques were used. Secondary data were collected from Saver Agricultural Office, different books and journals. The study revealed that 33.4% Peoples have been living in Gokulnagar for 15 years. And 36.5% people made their house with pucca building (single store) on the other hand 49.3% people used Tube-well for consumption of water in study area. In study area 39% people were found as a joint family member. From the educational perspective most of respondents were educated, whereas graduation (17.9%), H.S.C (25.4%), S.S.C (26.9%) and 20.9% of them completed their post-graduation level. Development issues like powerful external forces, including those of roads, better educational facilities, migration, improved communication, industrialization and the growth of marketing outlets- were found creating a rural landscape that is increasingly urban in character and rural life is being transformed. Alarming situation found out by this study is that congested housing pattern lead to improper land use throughout the investigated Gokulnagar village under of Dhaka district. The living standard of the people of study area was being changed for this situation.DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22177 J. Environ. Sci. & Natural Resources, 7(1): 241-247 2014